The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00024-010-0155-4
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Analysis and Expert Judgment in Seismic Hazard Analysis

Abstract: The large uncertainty associated with the prediction of future earthquakes is usually regarded as the main reason for increased hazard estimates which have resulted from some recent large scale probabilistic seismic hazard analysis studies (e.g. the PEGASOS study in Switzerland and the Yucca Mountain study in the USA). It is frequently overlooked that such increased hazard estimates are characteristic for a single specific method of probabilistic seismic hazard analysis (PSHA): the traditional (CornellMcGuire)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The most important root cause-the underestimation of the seismic and tsunami hazard-is not addressed at all. Despite the very poor hazard prediction results of traditional PSHA (Probabilistic Seismic Hazard Analysis), -nearly all recent large earthquakes (Tohoku earthquake and tsunami, Haiti (2010), Sichuan (2008), L'Aquila (2009) were underestimated in PSHA maps) the method is still in use and widely endorsed internationally although their systematic errors are very well-known as for instance is outlined in Klügel (2007Klügel ( , 2008Klügel ( , 2011. If this important lesson is not learned catastrophes like in Fukushima may repeat.…”
Section: Lessons Not Yet Learned From Fukushimamentioning
confidence: 99%
See 1 more Smart Citation
“…The most important root cause-the underestimation of the seismic and tsunami hazard-is not addressed at all. Despite the very poor hazard prediction results of traditional PSHA (Probabilistic Seismic Hazard Analysis), -nearly all recent large earthquakes (Tohoku earthquake and tsunami, Haiti (2010), Sichuan (2008), L'Aquila (2009) were underestimated in PSHA maps) the method is still in use and widely endorsed internationally although their systematic errors are very well-known as for instance is outlined in Klügel (2007Klügel ( , 2008Klügel ( , 2011. If this important lesson is not learned catastrophes like in Fukushima may repeat.…”
Section: Lessons Not Yet Learned From Fukushimamentioning
confidence: 99%
“…In Klügel (2011) I provided a detailed review of the associated methods. It was clearly demonstrated that the results of these methods are ambiguous.…”
Section: The Use Of Logic Trees and The Aggregation Of Expert Opinionsmentioning
confidence: 99%
“…The data presented in Table 2 was used and the associated site intensities were calculated based on the equations used for the development of the Swiss national earthquake catalogue [24]. The general renewal process model (GRP) as described in detail [25] and as implemented in the reliability software tool WEIBULL++7© [26] was applied for the analysis. The type I GRP model was found to provide the best prediction of past earthquake observations.…”
Section: Risk Analysis: Loss Of Productionmentioning
confidence: 99%
“…Applying a Poissonian assumption for earthquake recurrence [1], this probability of exceedance is usually converted into a return period. The latter is frequently incorrectly interpreted as a temporal characteristic of the recurrence of earthquake ground motion accelerations although there is no basis for this interpretation and the above assumption [3].…”
Section: Introductionmentioning
confidence: 99%
“…SEJ is an established technique for probabilistic risk assessment (Apostolakis 1990;Cooke 1991;Aspinall 2010) and consequence analysis (Cooke and Goossens 2000). It has previously been used for several environmental applications including assessments of the likelihood of natural disasters (for example, volcanic eruption, dam failure; Aspinall and others 2003;Klugel 2011), the consequences of nuclear accidents (Cooke and Goossens 2000), the drivers of climate change (Morgan and others 2006;Lenton and others 2008), expected changes in fisheries and marine ecosystems (Rothlisberger and others 2010;Teck and others 2010) and increases in mortality attributable to air pollution (Roman and others 2008). The method has not previously been used to assess the ecosystem-level impacts of invasive species.…”
Section: Introductionmentioning
confidence: 99%